2008
DOI: 10.1080/10428190802124281
|View full text |Cite
|
Sign up to set email alerts
|

Delays in referral and diagnosis for chronic hematologic malignancies: A literature review

Abstract: To better understand the extent of diagnostic and referral delays from primary care providers (PCPs) for chronic hematologic malignancies, causes of these delays, and their possible effects on cancer outcomes, an extensive review of the literature was performed. Over 50 studies were reviewed, including many that concern delays in referral and diagnosis for solid tumors, as there was only sparse literature on delays specific to the liquid tumors. Delays for some chronic hematologic malignancies have been docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…In a review of diagnostic delays reported in multiple countries, we identified no variables consistently associated with delays [26]. Further, we found no empirical studies that examined diagnostic delays in multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%
“…In a review of diagnostic delays reported in multiple countries, we identified no variables consistently associated with delays [26]. Further, we found no empirical studies that examined diagnostic delays in multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%
“…21 The reasons for late presentation of haematologic malignancies in our setting are multi-factorial, and ranges from patient factors, to delays in referral as well as paucity of adequate screening, diagnostic and therapeutic facilities. 10, 2527 …”
Section: Discussionmentioning
confidence: 99%
“…9 The outcomes in haematologic malignancies can also vary by time of presentation, type of the disease, stage of the tumour at presentation, other co-morbidities, availability and quality of the access to medical care. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, clinicians may need to make additional testing requests. Lack of diagnostic experience in a particular clinic[19] coupled with variable clinical presentations [20-23] may delay referral to a specialist or completion of a diagnostic workup. As diagnostic technologies evolve, differences in clinician awareness of updated information may lead to inconsistent test ordering and variable interpretation of test results [9,10,24].…”
Section: Introductionmentioning
confidence: 99%